PEMANFAATAN ALAT PENGUPAS NANAS DENGAN SISTEM PRESS UNTUK PEDAGANG NANAS MADU DI TANGERANG SELATAN - Gunawan, Harjadi; Darmawan, Marten; Soewono, Arka Dwinanda; Basoeki, Prita Dewi; Nahak, Demetrio; Pote, Juan William; Tobing, Sheila (Jurnal Abdimas Bina Bangsa, 2025)
The traditional process of peeling a pineapple using a knife is complex and time-consuming. Therefore, a specialized peeler is needed to increase the productivity of honey pineapple peddlers located in the Cisauk area, South Tangerang. The objective of this service activity is to design a prototype of a pineapple peeler using press technology that can peel pineapples more quickly and efficiently, and produce more precise and uniform cuts. This pineapple peeler consists of a knife ring with a diameter of 11-12 cm. It is also equipped with a spring system with an inner diameter of 30 mm, an outer diameter of 41 mm, and a length of 206 mm which functions as part of the mechanism to automatically return the knife ring and pressing lever to their original position. The knife and spring components are made from food-grade Stainless Steel 316 and 304, rsepectively. The test results show that the prototype peeler can peel honey pineapple measuring 10-12 cm in diameter in an average time of 13.11 seconds. It is hoped that the use of this peeler can help increase the productivity of small pineapple peddlers, as well as reduce their burden and work risks.